2010
DOI: 10.3892/mmr_00000302
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma-associated protein markers investigated by MALDI-TOF MS

Abstract: Abstract. Hepatocellular carcinoma (Hcc) is one of the most common types of cancer worldwide. The initial hepatocellular alterations that precede the appearence of Hcc include chronic viral hepatitis/cirrhosis, foci of phenotypically altered hepatocytes and, subsequently, dysplastic hepatocytes that form foci and nodules. These changes cause a discrepancy in the microenvironment of liver cells, which may result in changes in the protein expression profile of the cells. The aim of the present study was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 13 publications
2
33
0
Order By: Relevance
“…This rich source of circulating AAT is primarily produced by hepatocytes within the liver (Rogers et al 1983); however, other cells, such as epithelial cells (Cichy et al 1997), monocytes , macrophages and neutrophils du Bois et al 1991), intestinal epithelial cells (Molmenti et al 1993), alpha and delta cells of human pancreatic islets (Bosco et al 2005) and cancer cells (Chen et al 2010) have also been shown to produce smaller quantities of the protein. The AAT molecule is synthesised as a single polypeptide chain that is post-translationally modified by glycosylation through the addition of N-glycosidically linked oligosaccharides (Kolarich et al 2006a, b) that exist as di-, tri-or tetra-antennary structures (Kolarich et al 2006b) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This rich source of circulating AAT is primarily produced by hepatocytes within the liver (Rogers et al 1983); however, other cells, such as epithelial cells (Cichy et al 1997), monocytes , macrophages and neutrophils du Bois et al 1991), intestinal epithelial cells (Molmenti et al 1993), alpha and delta cells of human pancreatic islets (Bosco et al 2005) and cancer cells (Chen et al 2010) have also been shown to produce smaller quantities of the protein. The AAT molecule is synthesised as a single polypeptide chain that is post-translationally modified by glycosylation through the addition of N-glycosidically linked oligosaccharides (Kolarich et al 2006a, b) that exist as di-, tri-or tetra-antennary structures (Kolarich et al 2006b) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…While the mechanism responsible for its complex hepatocarcinogenesis is still under investigation, rapid hepatocellular carcinoma tumor proliferation due to dysregulation of the cell-cycle proteins is clear. Herein, we have taken advantage of the rapid proliferating nature of tumor cells in general and the high levels of hAAT expression found in hepatocellular carcinoma (30)(31)(32) and generated an effective vector system whereby transgene expression is dependent on the activation of two endogenously regulated promoters, i.e., 4ÂApoE/hAAT liver-specific promoter and recombinant human cyclin A2. In the context of oncolytic HSV-1, the 4ÂApoE/hAAT liver-specific promoter has also been shown to drive the expression of complementary sequences of selected miRNAs exclusively in hepatocellular carcinoma (33).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, down-regulation of miR-1 and miR-133a in human renal cell carcinoma resulted in up-regulation of the oncogenic TAGLN2 (30). Overexpression of TAGLN2 has been reported to serve as a potential biomarker for some cancer types, including colorectal cancer (31), hepatocellular carcinoma (32), and breast cancer (33,34). To our knowledge, the current study is the first study to report that urinary TAGLN2 can be used as a noninvasive biomarker for bladder cancer diagnosis and grade/stage discrimination.…”
Section: Comparison Of Tissue and Urine Proteomes In Bladder Canmentioning
confidence: 99%